Exploring craft in construction with short-term ethnography: reflections on a researcher's prior insight. Issue 5 (4th May 2022) - Brett, Richard; Thomson, Derek; Dainty, Andrew
Abstract: Ethnography offers a route to knowing about the everyday activities of construction workers, but its long duration is not always suited to the site environment or the researcher's resources and the workers themselves are constantly changing. Short-term ethnography is an alternative to the traditional format that permits a shorter length of fieldwork activity in return for intense engagement between the researcher and their participants. The rich points that make up an ethnographic account need to be actively sought in short-term ethnography. This can be achieved by utilizing the prior construction experiences of the researcher. The researcher enters the field with an emic insight that can be used to seek out events and allows the production of meaningful ethnography from a shorter, more intense fieldwork period, learning much from individual workers before they move on. Engagement extends beyond the onsite interactions through the use of video cameras to record everyday activities. Examples from two short-term ethnographies of two deliberately different sites explain how, in the search for craft traits among construction workers, the fieldworker is able to mobilize emic insight and craft theory to seek out rich points in everyday events which are typically serendipitous in nature. This account serves to provide a demonstration of how the very real tensions between the limitations of project context as a field site and the need for methodological rigour can be reconciled through careful attention to reflexive ethnographic practice.